Low‐Grade Dysplasia in Ulcerative Colitis: Risk Factors for Developing High‐Grade Dysplasia or Colorectal Cancer. (October 2015) - Choi, Chang‐ho Ryan; Ignjatovic‐Wilson, Ana; Askari, Alan; Lee, Gui Han; Warusavitarne, Janindra; Moorghen, Morgan; Thomas‐Gibson, Siwan; Saunders, Brian P; Rutter, Matthew D; Graham, Trevor A; Hart, Ailsa L
Abstract : OBJECTIVES: The aim of this study was to identify risk factors associated with development of high‐grade dysplasia (HGD) or colorectal cancer (CRC) in ulcerative colitis (UC) patients diagnosed with low‐grade dysplasia (LGD). METHODS: Patients with histologically confirmed extensive UC, who were diagnosed with LGD between 1993 and 2012 at St Mark's Hospital, were identified and followed up to 1 July 2013. Demographic, endoscopic, and histological data were collected and correlated with the development of HGD or CRC. RESULTS: A total of 172 patients were followed for a median of 48 months from the date of initial LGD diagnosis (interquartile range (IQR), 15–87 months). Overall, 33 patients developed HGD or CRC (19.1% of study population; 20 CRCs) during study period. Multivariate Cox proportional hazard analysis revealed that macroscopically non‐polypoid (hazard ratio (HR), 8.6; 95% confidence interval (CI), 3.0–24.8; P <0.001) or invisible (HR, 4.1; 95% CI, 1.3–13.4; P =0.02) dysplasia, dysplastic lesions ≥1 cm in size (HR, 3.8; 95% CI, 1.5–13.4; P =0.01), and a previous history of "indefinite for dysplasia" (HR, 2.8; 95% CI, 1.2–6.5; P =0.01) were significant contributory factors for HGD or CRC development. Multifocal dysplasia (HR, 3.9; 95% CI, 1.9–7.8; P <0.001), metachronous dysplasia (HR, 3.5; 95% CI, 1.6–7.5; P =0.001), or a colonic stricture (HR, 7.4; 95% CI, 2.5–22.1; P <0.001) showed only univariate correlation to development of HGD or CRC. CONCLUSIONS: Lesions that are non‐polypoid or endoscopically invisible, large (≥1 cm), or preceded by indefinite dysplasia are independent risk factors for developing HGD or CRC in UC patients diagnosed with LGD.